Evidence of shared and distinct functional and structural brain signatures in schizophrenia and autism spectrum disorder - Yuhui Du (Nature Portfolio, 2021)
Du et al used fMRI data from patients with schizophrenia (SZ) and autism spectrum disorder (ASD) to analyze multi-scale brain functional connectivity and cerebral grey matter density and volume. They demonstrated the presence of convergent and divergent changes in SZ and ASD that correlated with clinical features.